2017
DOI: 10.5740/jaoacint.16-0424
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Dinotefuran and Its Metabolites in Orange Pulp, Orange Peel, and Whole Orange Using Liquid Chromatography-Tandem Mass Spectrometry

Abstract: Determination of the polar characteristics of dinotefuran and metabolite residues in orange matrixes (orange pulp, orange peel, and whole orange) is difficult. Thus, the purpose of the present study was to develop an extraction method for the determination of dinotefuran and its metabolites in oranges by using liquid chromatography with tandem mass spectrometry (LC-MS/MS). Matrix suppression effects were observed for all analytes in the orange matrixes. The proposed method displayed satisfactory linearity (R2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Before photolysis (black traces), DNF (MW 202) shows a parent peak at m/z 203 corresponding to [DNF + H] + as well as a dimer ion at m/z 405 corresponding to [2DNF + H] + (data not shown). MS/MS analysis of m/z 203 (Figure S5) showed fragments at m/z 157, 129, and 113, consistent with the literature for DNF. …”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Before photolysis (black traces), DNF (MW 202) shows a parent peak at m/z 203 corresponding to [DNF + H] + as well as a dimer ion at m/z 405 corresponding to [2DNF + H] + (data not shown). MS/MS analysis of m/z 203 (Figure S5) showed fragments at m/z 157, 129, and 113, consistent with the literature for DNF. …”
Section: Resultssupporting
confidence: 86%
“…After photolysis (Figure , colored traces), product peaks corresponding to urea (UR DNF ) and desnitro (DN DNF ) derivatives appear, which are commonly observed for samples containing DNF and its metabolites. ,,, UR DNF (MW 158) is seen at m/z 159 corresponding to [UR DNF + H] + as well as at m/z 317 and m/z 361 (data not shown) corresponding to [2UR DNF + H] + and [UR DNF + DNF + H] + , respectively. The peak at m/z 158 corresponds to [DN DNF + H] + for the desnitro derivative DN DNF (MW 157).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Several types of research had been reported that QuEChERS or solid-phase extraction technology combined with gas chromatography-mass spectrometry (GC-MS), gas chromatography-nitrogen phosphorus detector (GC-NPD), gas chromatography-electron capture detector (GC-ECD), high-performance liquid chromatography-diode array detection (HPLC-DAD), high-performance liquid chromatography-ultraviolet detector (HPLC-UVD), ultra-high-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) and ultra-high-performance liquid chromatography coupled to Orbitrap mass spectrometry (UHPLC-Orbitrap-MS) could achieve the analysis of flonicamid, dinotefuran and its metabolites, separately. 5,9,10,16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In particular, the residual analysis and chronic dietary risk assessment of flonicamid on green tea, cabbage, cucumber, apple, potato, honeysuckle, cotton and paprika, 5,9,10,18-24 dinotefuran and its metabolites on cucumber, cotton, apple, Oryza sativa, eggplant, plum, orange, green tea, and melon 16,[25][26][27][28][29][30][31][32] have been carried out. However, to the best of our knowledge, studies on the degradation patterns and final residue levels of this mixture preparation on peach trees were still scarce so far, which were of great significance for the evaluation of its potential dietary intake hazards to consumers and for guaranteeing food safety.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these references selected only three or fewer sites to conduct field trials, and the samples collected from field sites were not adequately representative. Various studies have reported residue analysis of DIN, UF and DN in eggplant (Chen, Liu, et al, 2018), apples (Yu et al, 2017), rice (Li et al, 2017), wolfberry (W. Li, Shen, et al, 2019), orange (Yang et al, 2017), peach (Xu et al, 2021), cucumber (X. Chen, Dong, Xu, et al, 2015) and plum (Rahman et al, 2018) with methods such as (QuEChERS) coupled with HPLC–MS/MS or HPLC. However, very few papers have reported the residual analysis of DIN and its two metabolites in wheat.…”
Section: Introductionmentioning
confidence: 99%